Computational and In Vitro Analysis of Plumbagin’s Molecular Mechanism for the Treatment of Hepatocellular Carcinoma - Wei, Yanfei; Lin, Yuning; Chen, Wanjun; Liu, Shasha; Jin, Lijie; Huang, Delun (Frontiers in Pharmacology, 2021)
Abstract: Hepatocellular carcinoma (HCC) is the fifth most common malignant tumor and the second leading cause of cancer-related death in the world. Plumbagin (PL) is a small molecule naphthoquinone compound isolated from Plumbago zeylanica L that has important anticancer properties, but its mechanism still needs further investigation. In this study, we used a comprehensive network pharmacology approach to study the mechanism of action of PL in the treatment of HCC. The method includes the construction of multiple networks, and Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed to identify biological processes and signaling pathways. Subsequently, in vitro experiments were performed to verify the predicted molecular mechanisms obtained from the analysis based on network pharmacology. Network pharmacological analysis shows that PL may have an anti-HCC effect by mediating reactive oxygen species (ROS) to generate oxidative stress and to regulate the PI3K/Akt and MAPK signaling pathways. In vitro experiments confirmed that PL mainly mediates the production of ROS, regulates the PI3K/Akt and MAPK signaling pathways to promote cell apoptosis and autophagy, and shows significant therapeutic effects on HCC. In conclusion, our work proposes a comprehensive systems pharmacology approach to explore the potential mechanism of PL in the treatment of HCC.